2003
DOI: 10.1515/mamm.2003.67.2.225
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric variation of the common shrew, Sorex araneus, in different habitats

Abstract: Morphometric variation of the common shrew was studied in three different habitats (dry meadow, wet sedge bog, and floodplain forest) in Biatowieza, north-eastern Poland. Morphometric differentiation was examined by the use of 26 orthogonal mandibular measurements in 138 specimens. Comparison of mean values by discriminant functions in three studied samples of shrews revealed statistically significant differences (x 2 = 96.812, d.f. = 52, p = 0.0002). The discriminant function analysis performed on 26 morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 6 publications
0
9
0
1
Order By: Relevance
“…Variations in the common shrew Sorex araneus have been found both on cytogenetical and morphological levels, although the connection between the two is unclear (Dannelid 1991;Heikkila¨1989;Searle and Thorpe 1987;Wojcik et al 2003;Zima et al 1994). Bergman's rule has been found to be both supported (Nowak and Wolf 2004;Sulkava et al 1985;White and Searle 2007) and contradicted (Frafjord et al 1994;Kaikusalo and Tast 1994;Ochocinska and Taylor 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Variations in the common shrew Sorex araneus have been found both on cytogenetical and morphological levels, although the connection between the two is unclear (Dannelid 1991;Heikkila¨1989;Searle and Thorpe 1987;Wojcik et al 2003;Zima et al 1994). Bergman's rule has been found to be both supported (Nowak and Wolf 2004;Sulkava et al 1985;White and Searle 2007) and contradicted (Frafjord et al 1994;Kaikusalo and Tast 1994;Ochocinska and Taylor 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of Sorex araneus populations from Bia³owie¿a showed mixed associations of habitat and population differentiation. Wójcik (1991) and Wójcik et al (1996) concluded that chromosome and allozyme polymorphisms were related to environmental heterogeneity; however, morphometric differentiation of mandible shape was not (Wójcik et al, 2003). Previous studies of mandibular shape in the common shrew have found the greatest differentiation at higher hierarchical levels than the population, notably among species within the S. araneus-arcticus group and among karyotypic groups of S. araneus (Hausser & Jammot, 1974;Polly, 2006), whereas previous studies of epigenetic variation have found significant differentiation at the population level.…”
Section: Introductionmentioning
confidence: 99%
“…Several other studies of common shrews have also found relationships between mandible morphology and environmental variables, including latitude and habitat type (Hausser, 1984; Sulkava et al. , 1985; Wójcik et al. , 2003).…”
Section: Discussionmentioning
confidence: 92%